If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1 + X) = 2(2 + X) (1 * 4 + X * 4) = 2(2 + X) (4 + 4X) = 2(2 + X) 4 + 4X = (2 * 2 + X * 2) 4 + 4X = (4 + 2X) Add '-4' to each side of the equation. 4 + -4 + 4X = 4 + -4 + 2X Combine like terms: 4 + -4 = 0 0 + 4X = 4 + -4 + 2X 4X = 4 + -4 + 2X Combine like terms: 4 + -4 = 0 4X = 0 + 2X 4X = 2X Solving 4X = 2X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2X' to each side of the equation. 4X + -2X = 2X + -2X Combine like terms: 4X + -2X = 2X 2X = 2X + -2X Combine like terms: 2X + -2X = 0 2X = 0 Divide each side by '2'. X = 0 Simplifying X = 0
| 14=50x | | x+7=-61 | | -2x-8=-13x-4 | | -5=25x | | -16x=224 | | 111n-9=5n+27 | | 15*15x=144 | | (2x+3)x(3x-6)= | | 1.5(2a+1)=5(0.5a+0.3)+0.1 | | (0.8g+0.6-0.3)=(0.1-0.2h+0.8g) | | -x-5=3x+19 | | x^2+4*x-7=2*x-4 | | 2x-20=2x+10 | | 5x+(-2)=20 | | (5x-9)(2x+4)= | | -22=-7+3y | | -59+3x=2x+21 | | 5(0)+y=20 | | -7(-5n-2)=119 | | 42=34+q | | Log(x-6)=2 | | -1+6y=14 | | 8(4)(7)-9(3)+4(4)= | | 7x+5=5x-5 | | 10010001001002030+3-10= | | 3x+5=-8(6-5x) | | 11x-47-x=103 | | 4v=8v+32 | | 10m+12n+5m+3n+35= | | 2x-42-7x=84 | | 5x+2(1.5)=10 | | 49-9x+5x=27 |